2016
DOI: 10.1080/15402002.2016.1150279
|View full text |Cite
|
Sign up to set email alerts
|

Low-to-Moderate Alcohol Consumption is Associated With Hippocampal Volume in Fibromyalgia and Insomnia

Abstract: Fibromyalgia and chronic insomnia are frequently comorbid conditions with heightened sensitivity to painful stimuli, potentially subserved by the hippocampus. Recent evidence suggests moderate alcohol consumption is associated with reduced fibromyalgia symptom severity. We examined relationship between alcohol use, hippocampal morphology, fibromyalgia and/or insomnia symptom severity in 41 fibromyalgia patients (19 with insomnia). A 14-day diary of sleep, pain, and alcohol consumption was followed by structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Numerous neurotransmitter systems have been implicated with shared genetic underpinnings likely influencing neural adaptations in both AUD and chronic pain. Yet, to our knowledge, no studies have examined the neural circuitry of chronic pain and AUD in human clinical samples and we could only identify 2 studies that examined neural correlates of substance use among chronic pain patients (Boissoneault et al, ; Petre et al, ). For discussion of the overlapping neural adaptations and circuitry, we recommend prior reviews on the topic (Apkarian et al, ; Egli et al, ; Elman and Borsook, ; Yeung et al, ).…”
Section: Clinical Models To Investigate the Intersection Of Aud And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous neurotransmitter systems have been implicated with shared genetic underpinnings likely influencing neural adaptations in both AUD and chronic pain. Yet, to our knowledge, no studies have examined the neural circuitry of chronic pain and AUD in human clinical samples and we could only identify 2 studies that examined neural correlates of substance use among chronic pain patients (Boissoneault et al, ; Petre et al, ). For discussion of the overlapping neural adaptations and circuitry, we recommend prior reviews on the topic (Apkarian et al, ; Egli et al, ; Elman and Borsook, ; Yeung et al, ).…”
Section: Clinical Models To Investigate the Intersection Of Aud And Pmentioning
confidence: 99%
“…Boissoneault and colleagues () examined associations between alcohol use and hippocampal volume among 40 women with fibromyalgia (45% of whom also had insomnia). Results indicated that any alcohol consumption over the 14 days prior to a magnetic resonance imaging (MRI) scan (average drinks/d <1 drink) was associated with significantly lower pain intensity and greater hippocampal volume, bilaterally, as compared to abstainers.…”
Section: Clinical Models To Investigate the Intersection Of Aud And Pmentioning
confidence: 99%
“…were self-reported using-Mood and pain were self-reported using (a) the Beck Depression Inventory II (BDI-II) to capture depressive symptoms over the past two weeks (Beck, 1996), (b) the Graded Chronic Pain Scale (GCPS) (Von Korff et al, 1992), which captures pain severity and is widely used in medical pain research, and (c) the Pain Catastrophizing Scale (PCS) (Sullivan et al, 1995) which focuses on the emotional experience of physical pain. The first three items of the GCPS yielded mean pain intensity calculated as the average of current pain intensity, worst pain intensity, and average pain intensity over the last six months, each rated on a 0 to 10 scale with the endpoints of "no pain" (0) and "a lot of pain" (10). Exploratory analyses were conducted examining clinical and demographic differences between pain grades, which are categorical.…”
Section: Mood and Painmentioning
confidence: 99%
“…subjective pain lasting longer than 3 months) report higher levels of alcohol use and are more likely to have an alcohol use disorder (AUD) relative to the general population (Hoffmann et al, 1995;Vowles et al, 2018). Among treatmentseeking individuals with AUD, 30-50% report chronic, recurrent pain (Boissoneault et al, 2017;Caldeiro et al, 2008;Jakubczyk et al, 2015) and those who do experience pain spend fewer days in AUD treatment and have a lower likelihood of abstinence from alcohol after treatment (Jakubczyk et al, 2016;Witkiewitz et al, 2015). While the association between pain and alcohol use is complex, how pain interacts with other proximal predictors of alcohol consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%